MICROCONTROLLER BASED LAPTOP COOLING SYSTEM - MUHAMAD SHUKRI, NURUL AKMAL (Universiti Teknologi Petronas, 2008)
The main objective of this project is to deliver an implementation of microcontroller based laptop cooling system. This project involves the development of a better cooling system for laptop which includes the temperature monitoring feature, and also alarm and LEDS as indicators. The microcontroller programming, sensor integration, circuit design and troubleshooting were the major parts of this project. Upon this project completion, a working prototype which in a form of cooling pad with 3 fans, temperature sensor and indicators is delivered. The prototype working mechanism is based on two threshold temperatures which will control the output of the system. If the input from the temperature sensor exceeds the first threshold temperature, the fans will be switched on to start the cooling mechanism. When the second threshold temperature has been exceeded, the alarms and other indicators will be turned on to warn users of overheating. The deliverables outlined, which are microcontroller programming, and hardware prototyping has been fulfilled. Hence, the requirement of this project which is to deliver a prototype of microcontroller-based external laptop cooling system has been achieved.